Analisis Studi Literatur Pengkajian Algoritma Dan Pemrograman Mahasiswa Di Revolusi Industri Teknologi Pada Jurusan Pendidikan Matematika - Miftah Khairiyah SM; Yahfizham Yahfizham (International Forum of Researchers and Lecturers, 2023)
Particularly in the context of the technological industrial revolution, information technology is developing more quickly. We cannot prevent technological development in this life because it will inevitably follow scientific advancements in science. Educational technology has the power to transform traditional teaching methods into innovative ones. Even though the term